PENGARUH PASTA GIGI ENZIMÂ® ORTHODONTIC TERHADAP HALITOSIS PADA PEMAKAI ALAT ORTODONTIK CEKAT - , KADEK ASRI ASMITA PRADNYANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fixed orthodontics appliance usage increases difficulty of oral hygiene maintenance caused by attachment of food debris and plaque. Attachment of food debris and plaque can cause halitosis. Halitosis is bad breath that caused by volatile sulfur compounds (VSCs). Brushing teeth with toothpaste can reduce halitosis. Enzim Â® Orthodonticstoothpaste is claimed to reduce this problems in fixed orthodontics patients. The aim of this study was to know the effect of Enzim Â® Orthodonticstoothpaste to halitosis in fixed orthodontics patients. The subject of this study was 15 fixed orthodontics patients. This study was consisted by brushing without toothpaste as control and brushing with Enzim Â® Orthodontics. The level of halitosis was measured 2 hours after brushing. The measurement was done by Oral Chromaâ¢. Oral Chromaâ¢ show three kindof volatile sulfur compounds. Data were analyzed using Wilcoxon test. The result showed significant difference after brushing with Enzim Â® Orthodonticscompare to brushing without toothpaste. Wilcoxon test showed significant difference of volatile sulfur compounds. The conclusion of this study was Enzim Â® Orthodonticscan reduce halitosis in fixed orthodontic patients.